Temporal and spatial variability of immunosuppressive therapies in transplant patients: An observational study in Italy - Marino, Maria Lucia; Rosa, Alessandro C.; Finocchietti, Marco; Bellini, Arianna; Poggi, Francesca R.; Massari, Marco; Spila Alegiani, Stefania; Masiero, Lucia; Ricci, Andrea; Bedeschi, Gaia; Puoti, Francesca; Cardillo, Massimo; et al. (Frontiers in Transplantation, 2023)
In immunosuppression after transplantation, several multi-drug approaches are used, involving calcineurin inhibitors (CNI: tacrolimus-TAC or cyclosporine-CsA), antimetabolite (antiM), mammalian target of rapamycin inhibitors (mTORi) and corticosteroids. Data on immunosuppressive therapy by organ and its space-time variability are lacking. An Italian multicentre observational cohort study was conducted using health information systems. Patients with incident transplant during 2009-19 and resident in four regions (Veneto, Lombardy, Lazio, Sardinia) were considered. The post-transplant immunosuppressive regimen was evaluated by organ, region and year. The most dispensed regimen was triple drug therapy for kidney (TAC+antiM+corticosteroids=41.5%) and heart (CsA+antiM+corticosteroids=36.6%) and double drug therapy for liver recipients (TAC+corticosteroids=35.4%). Several differences among regions and years emerged with regard to agents and number of drugs used. High heterogeneity in immunosuppressive therapy post-transplant was found. Further studies are needed in order to investigate reasons of this variability and to evaluate the risk-benefit profile of treatment schemes adopted in the clinical practice.